The Philippines confronts China in the South China Sea: Power politics vs. liberalism-legalism - De Castro, Renato Cruz (Animo Repository, 2015)
Using the Scarborough Shoal standoff between China and the Philippines as a case study, in this article I examine two approaches to addressing territorial disputes-power politics and liberalismlegalism. China, a major power, uses realpolitik to press its expansive claim in the South China Sea. The Philippines, a small power, adopts the liberal-legal approach that seeks to balance against China. During the standoff, China drove the Philippines out of the shoal, though stopping short of an armed clash, and effected a de facto occupation of the contested area. As a countermeasure, the Philippines filed a statement of claim with the International Tribunal for the Law of the Sea. The confrontation was a test of Thucydides's age-old aphorism that "the strong do what they have the power to do, and the weak accept what they have to accept".